Acoustic emission during run-up and run-down of a power generation turbine. - Zuluaga-Giraldo, C.; Mba, David; Smart, M. (Elsevier, 2004)
The measurement of acoustic emission (AE) activity at the bearings of power generation turbines is evolving into a viable complementary diagnostic technique especially adept at indicating the early stages of shaft-seal rubbing. This paper reports on an ongoing investigation on the application of acoustic emission for shaft-seal rub detection in power generation turbines. A pre- requisite in developing such a technique requires an understanding of the operational AE background noise. The detection of shaft-seal, and blade-case, rubbing with AE has been reported [Electrical Eng. Japan 110 (2) (1990); Joint ASME/IEEE Power Generation Conference, October 4–8, 1981, St. Louis, MI, USA; International Conference on Condition Monitoring. Oxford, UK, July 2–4, 2003]. In these instances, the observations of AE activity were associated with particular dynamic and process conditions known to cause such defects. However, the effect of variations of turbine loading on AE activity is unknown. This report presents observations of AE activity during the run-up and run-down of a 500 MW steam turbine and is the first known document detailing correlations between AE, vibration and turbine load
Keywords: Acoustic emissions; Blade-case rubbing; Condition monitoring; Power generation turbines; Shaft-seal rubbing